Shortened questionnaires to assess anxiety and depression during in-hospital rehabilitation: clinical validation and cutoff scores - Bertolotti G; Moroni L; Burro R; Spanevello A; Pedretti RFE; Giorgetti G (Neuropsychiatric Disease and Treatment)
Giorgio Bertolotti,1 Loretta Moroni,1 Roberto Burro,2 Antonio Spanevello,3 Roberto FE Pedretti,4 Giandomenico Giorgetti5 1Psychology Unit, Salvatore Maugeri Foundation, IRCCS, Scientific Institute, Tradate, 2Department of Human Sciences – University of Verona, Verona, 3Department of Cardiology, 4Division of Pulmonary Disease, 5Department of Neuromotor Rehabilitation, Salvatore Maugeri Foundation, IRCCS, Scientific Institute of Tradate, Italy Background: A postacute phase needs reliable routine screening instruments in order to identify the patients to be referred for a clinical interview with a psychologist. The aim of this study was to estimate the clinical cutoff scores of the anxiety and depression questionnaires and their clinical validity using a gold standard. Methods: The study involved 177 patients with pulmonary, cardiac, or neurological disease undergoing in-hospital rehabilitation. Receiver operating characteristic curves were used to determine the best concordance between questionnaire’s scores and the gold standards. Results: There was a significant difference (P<0.001) between clinically anxious and depressed patients and nonclinical subjects. The receiver operating characteristic curve for anxiety indicated that the best area under the curve for State Anxiety Inventory is obtained with a cutoff point of 21 for males and 25 for females; for depression scores, the highest area under the curve for Depression Questionnaire-Reduced Form is obtained with a cutoff point of six for males and eight for females. Conclusion: Using appropriate cutoff values, the State Anxiety Inventory and Depression Questionnaire-Reduced Form allow psychologists to optimize early clinical intervention strategies selecting patients with significant needs. Keywords: anxiety, depression, questionnaire, sensitivity and specificity, rehabilitation